Effects of endotracheal suctioning duration cerebral oxygenation in preterm infants - Merter, Ozlem Selime; Dertli, Semiha; Taskin, Erdal; Aydin, Mustafa; Benli, Samet (Wiley, 2025)
AimThis study evaluates the effects of endotracheal suctioning duration on cerebral oxygenation and physiological parameters in preterm infants in intensive care.DesignProspective and observational s tudy.MethodIn this study, 51 preterm infants born at 28-34 weeks of gestation in NICU were evaluated. Cerebral oxygenation was measured before, during, and after endotracheal suctioning with near-infrared spectroscopy. Pain levels of the infants were with N-PASS scale.ResultsA negative correlation was found between the lowest cerebral oxygenation value during endotracheal suctioning and the duration of endotracheal suctioning. Cerebral oxygenation levels during endotracheal suctioning were lower than pre- and post-endotracheal suctioning levels. Higher cerebral oxygenation was observed in infants whose endotracheal aspiration time was less than 13 s. The duration of endotracheal suctioning was positively correlated with pain and cerebral oxygenation stabilization time.ConclusionProlonged endotracheal suctioning duration negatively affects cerebral oxygenation in preterm infants. The study suggests an optimal endotracheal suctioning duration under 13 s.Implications for the Profession and/or Patient CareProperly executed endotracheal suctioning, with the correct technique and knowledge, can alleviate the adverse physiological effects observed in preterm infants and contribute to routine nursing care in intensive care units.Reporting MethodThis study has been reported in line with STROBE checklists.Patient or Public ContributionNo patient or public contribution was required to design or undertake this research. Patients contributed only to the data collection.ImpactThis study contributes to defining the ideal endotracheal aspiration duration, as there is not enough data so far. It showed the effect of prolonged endotracheal aspiration time on cerebral oxygenation, pain and physiological parameters in preterm infants.
Keywords: cerebral oxygenation; endotracheal aspiration duration; nurse; preterm